Dietary carbohydrate utilization by the Malaysian Mahseer, Tor tambroides (Bleeker, 1854) - Ishak, Sairatul Dahlianis (2018)
This study was carried out to investigate the utilization of dietary carbohydrate by the Malaysian mahseer, Tor tambroides (Bleeker, 1854). Wild mahseer fingerlings were obtained from fish suppliers in Pahang and Kelantan. Different batches of fish were used in different feeding trials and they were acclimatized for three weeks before the start of these trials. The effects of different experimental diets on the growth performance, feed utilization efficiency, body nutrient composition, nutrient retention, liver and intestine morphology, and glucose-6-phosphate dehydrogenase (G6PD) gene expression were measured. This study also attempted to evaluate the physical properties of extruded diets using selected starch sources for suitability in mahseer feeding. In the first feeding trial, fish were fed four experimental diets containing four carbohydrate levels (15%, 20%, 25% and 30%) using food grade corn starch as the carbohydrate source for 10 weeks. The best growth performance was observed in fish fed 20-25% dietary carbohydrate. Using a second-order polynomial regression analysis on the fish growth, the optimal dietary carbohydrate requirement of Malaysian mahseer was determined at 23.44%. Subsequent feeding trials were then based on this optimum level. In the second study, three locally grown starch sources, sago (Metroxylon sagu), cassava (Manihot esculenta) and taro (Colocasia esculenta) were tested as replacement for imported corn starch in the production of extruded feed for mahseer. Results showed that sago starch gave good expansion ratio and floatability and thus suitable for the production of floating mahseer feed. These feeds were then fed to mahseer juveniles for 10 weeks to evaluate the suitability of these starches as dietary carbohydrate and energy source for the Malaysian mahseer. Results showed that fish fed with corn starch and taro starch performed significantly better (P<0.05) than those fed sago and cassava starch. However, fish fed corn starch had the highest body lipid, lipid retention, and intraperitoneal fat indicating high conversion of carbohydrate to lipid compared to taro starch. Therefore, taro starch seemed to be the best candidate as a full or partial replacement of corn starch for the production of extruded feed for this species. The third feeding trial was conducted for 12 weeks to determine the effects of three forms of carbohydrates (starch, disaccharide sucrose and monosaccharide glucose) on the growth performance, feed utilization efficiency, body composition, nutrient retention, and liver and intestine morphology of mahseer. Best performance was observed in fish fed starch which suggested that mahseer benefited from higher complexity of carbohydrates compared to simple carbohydrates. The final feeding trial was conducted for 10 weeks to evaluate the effect of dietary carbohydrate level and form on the regulation of G6PD gene in mahseer. Fish were fed experimental diets prepared from the first and third feeding trials. Using real time PCR assays, the mRNA expression of G6PD gene in fish liver was estimated. Results showed that G6PD gene expression was significantly elevated (P<0.05) in the liver of fish fed 20% carbohydrate and maximum G6PD expression was achieved at 22.2% carbohydrate level which was very close to the optimal dietary carbohydrate requirement obtained in the first experiment. Among fish fed different carbohydrate forms, the highest G6PD gene expression (P<0.05) was observed in fish fed glucose. Dietary carbohydrate level and form influenced blood glucose level in mahseer which directly regulated the mRNA expression of G6PD gene during carbohydrate metabolism. A 20-25% dietary carbohydrate inclusion was recommended for the Malaysian mahseer. A higher or lower inclusion would affect the fish growth. This fish preferred dietary starch with corn and taro starches giving a good growth. High G6PD gene expression indicated increased carbohydrate metabolism and blood glucose level were due to the increasing dietary carbohydrate level. In conclusion, this present study strongly indicated that the Malaysian mahseer has a moderate ability in utilizing dietary carbohydrate inclusion level with a preference for soluble polysaccharides and a limited ability in utilizing starch sources.